North Korea, 2009-2012 : a guide to economic and political developments - Jeffries, Ian. (Milton Park, Abingdon, Oxon : Routledge, 2013)
'North Korea continues to be a country of great concern internationally, where future developments are uncertain, especially as a result of the succession to the leadership of Kim Jong-un following the death of Kim Il-sung. It is also a country which is relatively unknown and relatively little studied. This book provides a comprehensive, detailed survey of economic and political developments in the last few years. As such it provides many insights into the current trends which are likely to shape the country's future direction'--
Includes bibliographical references (p. [915]-918) and index.
Keywords: Korea (North) -- Politics and government; Korea (North) -- Economic conditions; Korea (North) -- Foreign economic relations; Korea (North) -- Economic policy